Cytotoxicity Test of Black Garlic (Allium Sativum L.) Ethanol Extract Using BSLT Method (Brine Shrimp Lethality Test) - Falah Rambe, Raudhotul; Ridwanto; H., Fathur Rahman; Daulay, Anny Sartika; Zulmairani (CV. Nusantara Scientific Medical, 2025)
Cancer is an abnormal condition of cells or a group of cells experiencing uncontrolled growth. In the last decade, the use of medicinal plants has tended to increase in line with the development of the herbal or traditional medicine, pharmaceutical, cosmetic, and food and beverages. There are various kinds of plants that can be used as anti-cancer treatments, one of which is black garlic. Black garlic is an ingredient made from garlic at a certain temperature and humidity. The objective of this research was to determine the phytochemical content of black garlic and to evaluate its toxicity level (LC50) using the Brine Shrimp Lethality Test (BSLT) method, by calculating the number of deaths of Artemia salina Leach larvae with Lethal Concentration 50 (LC50) as the parameter. Black garlic extract variation, chemical content, characterization, and cytotoxicity tests were variables in the research. Black garlic contains several secondary metabolite compounds namely alkaloids, flavonoids, glycosides, and steroids. The regression equation obtained was y = 1.5939x + 0.919, with an LC50 value of 363.2453 μg/mL. These results concluded that black garlic ethanol extract had a toxic effect on Artemia salina larvae.